A macro- and micronutrient-fortified complementary food supplement reduced acute infection, improved haemoglobin and showed a dose–response effect in improving linear growth: a 12-month cluster randomised trial. (2019) - Ghosh, Shibani A.; Strutt, Nicholas R.; Otoo, Gloria E.; Suri, Devika J.; Ankrah, Judith; Johnson, Thomas; Nsiah, Paul; Furuta, Chie; Murakami, Hitoshi; Perera, Gillian; Chui, Kenneth; Bomfeh, Kennedy; et al.
Abstract: Inadequate protein quality may be a risk factor for poor growth. To examine the effect of a macronutrient–micronutrient supplement KOKO Plus (KP), provided to infants from 6 to 18 months of age, on linear growth, a single-blind cluster-randomised study was implemented in Ghana. A total of thirty-eight communities were randomly allocated to receive KP (fourteen communities, n 322), a micronutrient powder (MN, thirteen communities, n 329) and nutrition education (NE, eleven communities, n 319). A comparison group was followed cross-sectionally ( n 303). Supplement delivery and morbidity were measured weekly and anthropometry monthly. NE education was provided monthly. Baseline, midline and endline measurements at 6, 12 and 18 months included venous blood draws, diet, anthropometry, morbidity, food security and socio-economics. Length-for-age Z -score (LAZ) was the primary outcome. Analyses were intent-to-treat using mixed-effects regressions adjusted for clustering, sex, age and baseline. No differences existed in mean LAZ scores at endline (−1·219 (sd 0·06) KP, −1·211 (sd 0·03) MN, −1·266 (sd 0·03) NE). Acute infection prevalence was lower in the KP than NE group ( P = 0·043). Mean serum Hb was higher in KP infants free from acute infection (114·02 (sd 1·87) g/l) than MN (107·8 (sd 2·5) g/l; P = 0·047) and NE (108·8 (sd 0·99) g/l; P = 0·051). Compliance was 84·9 % (KP) and 87·2 % (MN) but delivery 60 %. Adjusting for delivery and compliance, LAZ score at endline was significantly higher in the KP v. MN group (+0·2 LAZ; P = 0·026). A macro- and micronutrient-fortified supplement KP reduced acute infection, improved Hb and demonstrated a dose–response effect on LAZ adjusting consumption for delivery.